2020
DOI: 10.3390/ijerph17217847
|View full text |Cite
|
Sign up to set email alerts
|

Global to USA County Scale Analysis of Weather, Urban Density, Mobility, Homestay, and Mask Use on COVID-19

Abstract: Prior evaluations of the relationship between COVID-19 and weather indicate an inconsistent role of meteorology (weather) in the transmission rate. While some effects due to weather may exist, we found possible misconceptions and biases in the analysis that only consider the impact of meteorological variables alone without considering the urban metabolism and environment. This study highlights that COVID-19 assessments can notably benefit by incorporating factors that account for urban dynamics and environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 43 publications
(55 reference statements)
5
48
0
Order By: Relevance
“…The weather variables may also satisfy the second (exclusion restriction) and third (ignorability) assumptions. Studies have shown that, after controlling for sociodemographic factors, weather alone had a negligible effect on the spread of COVID-19 across the world [ 41 ]. In other words, the correlation between weather and COVID-19 found in some studies [ 42 ] may arise because of the influence of weather on people’s behavior, rather than on the virus itself.…”
Section: Data and Empirical Strategymentioning
confidence: 99%
“…The weather variables may also satisfy the second (exclusion restriction) and third (ignorability) assumptions. Studies have shown that, after controlling for sociodemographic factors, weather alone had a negligible effect on the spread of COVID-19 across the world [ 41 ]. In other words, the correlation between weather and COVID-19 found in some studies [ 42 ] may arise because of the influence of weather on people’s behavior, rather than on the virus itself.…”
Section: Data and Empirical Strategymentioning
confidence: 99%
“…Background : As the pandemic has engulfed the globe, affecting human activities on an unprecedented level, and concerns that Covid-19 may become endemic in the entire population, as other coronavirus infections have [ 4 ], the issue of seasonality must be unambiguously settled, especially as we are now approaching a full year of the epidemic expansion [ 7 ]. Other factors such as population density [ 8 ] or public health measures [ 9 ] have been seen as critical and thus challenged notions of seasonality of Covid-19, intertwined with irregular seasonal parameters such as humidity and air temperature [ 10 ]. Yet, recent research points to strong seasonal forcing of respiratory diseases that are modulated by environmental factors [ 11 ], an element that supports a similar cycle for Covid-19 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Guo et al looked at meteorological factors and Covid-19 incidence in 190 countries and concluded that a higher temperature was associated with a lower incidence of Covid-19 [89]. Ward et al determined that humidity has a significant effect on SARS-Cov2 spread in Australia [90], but Jamshidi et al did not find that weather was a significant factor [91]. Note that many meteorological studies examined absolutes of humidity and temperature, not fluctuations.…”
Section: Resultsmentioning
confidence: 99%